Quality Analysis of the Final Examination Instrument and Its Implication for Student Learning Outcomes in the Fundamentals of Physics II - Prawitasari; Suwasono, Purbo; Sutopo, Sutopo; Ananingtyas, Ratika Sekar Ajeng; Rohmiati, Dyah Palupi (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2025)
The low student learning outcomes in the Fundamentals of Physics II raise concerns about the quality of the evaluation instrument used to measure the students’ achievement. This study aims to analyze the quality of the Final Semester Examination (UAS) instrument and its relation with students’ learning outcomes. The subjects of this study were 53 second-semester students from the Department of Physics, Universitas Negeri Malang. The evaluation instruments consisted of 30 multiple-choice questions. The items were analyzed using PSPP statistical software, which functions similarly to SPSS. The analysis involved validity testing using the Pearson Correlation Method, reliability testing using Cronbach’s Alpha, the discrimination power and difficulty indices. The results showed that 50% of the items were valid, the instrument’s reliability was moderate with a Cronbach’s Alpha value of 0.60, and only 10% of the items had very good discrimination power, while most (63.4%) were categorized as low to negative. In terms of difficulty, 53.3% of the items were classified as difficult, 20% as moderate, and 26.7% as easy. These findings indicate that the low student learning outcomes are influenced not only by internal factors but also by the quality of the evaluation instrument. So, this study not only test the validity and reliability of the test items but also explores how the question construction can affect learning achievements. This study offers new insights for lecturers to design more accurate instruments that can truly reflect students’ ability, especially in the Fundamentals of Physics II course.